Hypotensive effect of Gentiana floribunda is mediated through Ca antagonism pathway - Khan, A.; Mustafa, Mohd Rais; Khan, A.U.; Murugan, D.D. (2012)
Background: Gentiana floribunda was investigated for the possible hypotensive and vasodilator activities in an attempt to rationalize its traditional use in hypertension. Methods: The crude extract of Gentiana floribunda (Gf.Cr) was studied in anaesthetized rats and isolated thoracic aorta tissues. Results: Gf.Cr which tested positive for presence of flavonoids, saponins, sterols, tannins and terpenes caused dose-dependent (3.0-100 mg/kg) fall in arterial blood pressure (BP) of rats under anaesthesia. In rat aortic ring preparations denuded of endothelium, Gf.Cr at concentration range of 1.0-10 mg/mL relaxed high K+ (80 mM) and phenylephrine (PE, 1 muM)-induced contractions and shifted Ca++ dose--response curves to right, similar to that caused by verapamil. It also suppressed PE (1 muM) control peak responses at 0.3-1.0 mg/mL, obtained in Ca++-free medium, as exhibited by verapamil. Pre-treatment of tissues with Gf.Cr produced rightward non-parallel shift of PE-curves with decline of maximum contractile response. The vasodilator effect of Gf.Cr was endothelial-independent, as it was not blocked by Nomega-nitro-L-arginine methyl ester hydrochloride, atropine and indomethacin in endothelium-intact aortic tissues. Conclusions: These data indicate that BP-lowering action of Gentiana floribunda occurred via Ca++ antagonism (inhibition of Ca++ ingress and release from intracellular stores), which provides pharmacological basis to justify its effectiveness in hypertension.